Effect of information communication technology skills on reduction of unemployment in Ibadan metropolis (2016)
The study examined the Effect of Information Communication Technology skills on youth unemployment reduction in Ibadan Metropolis, Oyo State. Data were collected from 350 respondents from Ibadan North Local government areas in Oyo State through purposive sampling method. Descriptive survey research design was use. The research instrument was a set of questionnaire tagged: “Effect of Information Communication Technology Skills on Reduction of Unemployment Rating Scale” (ICTSURS). Four research questions were raised and answered. Data obtained were analysed through simple percentages and cross tabulation. The findings showed that Information Communication Skills have improved socio-economic well-being of youths in terms of Job Creation, improved knowledge, improved financial Status and better resource sharing among youths